Long-term monitoring of post-fire above ground biomass recovery in a lowland dipterocarp forest in East Kalimantan, Indonesia - Toma, T.; Ishida, A.; Matius, P. (2005)
Between 1988 and 2000, changes in the above-ground biomass (AGB) of trees in an East Kalimantan lowland forest, damaged by fires in 1982-83 and 1998, were estimated using allometric functions and an annual inventory of stem diameter. The original vegetation of the study site was lowland dipterocarp forest which has since been affected by selective logging and wild fires. The 1982-83 fire killed large trees of primary species and the opened sites became dominated by a few pioneer species. Between 1988 to 1997, a few pioneer tree species, namely Macaranga spp., dominated a heavily disturbed stand (HDS). Primary tree species that survived the 1982-83 fire dominated a lightly disturbed stand (LDS). A moderately disturbed stand (MDS) contained vegetation intermediate between the HDS and the LDS. In 1997, there were 553, 499 and 356 trees ha-1 in the HDS, MDS and LDS, respectively. Macaranga trees accounted for 70%, 40% and 11% of the number of total trees in the HDS, MDS, and LDS, respectively. In 1997, the AGB of trees in the HDS, MDS, and LDS was 117, 280, and 315 Mg ha-1, respectively. The proportion of biomass accounted for by Macaranga trees for the HDS, MDS, and LDS was 34%, 8% and 1%, respectively. The pioneer trees did not compensate for the loss of aboveground biomass resulting from the death of large primary trees. The fire in 1998 again decreased AGB of the stands. In 2000, the AGB of trees in the HDS, MDS, and LDS was 27, 106, and 219 Mg ha-1, respectively. The sites opened up by the 1998 fire were covered with the pioneer seedlings and seemingly dominated by the pioneer trees with more number of stems per ha, but lower biomass as compared to the original forest (> 400 Mg ha-1).